The 2018 NCSA presidential address: the audience of executions. Issue 4 (2nd October 2018) - Linders, Annulla
ABSTRACT: Capital punishment occupies a precarious position in the modern democratic state. Much scholarship has addressed the political and judicial dilemmas associated with the death penalty. I focus on the execution itself as a fraught state activity and place the analytical spotlight on the audience of executions. The audience of executions is a critical component of executions and has played an important role in the transformation of capital punishment over the past 200 years. I use three modal forms, or ideal types, of the execution audience—the crowd, professional witnesses, and family members of murder victims—to highlight the ways in which the audience provides the American death penalty with some of its key meanings, contradictions, and pressures to change. All three audience forms have coexisted since the early nineteenth century, but their respective roles in the execution drama have changed dramatically as have the meanings generated by their presence.